The Utilization of the Potential of Employees in Specific Jobs as an Instrument of Company Competitiveness Increase - Mandysová, Michaela; Kožená, Marcela (Univerzita Palackého v Olomouci, 2021)
This paper's aim is to analyze the potential of the workforce in the context of how to determine its work effectiveness to increase the competitiveness of corporate organizations. The tools for effective job securing, i.e., job analysis (personnel audit) or eventually profesiography, are not sufficiently exploited. Within the theory, there is no clearly defined boundary between the job analysis and the job function audit. The analysis will first focus on the key theoretical bases and the comparison of the current empirical approaches to the matter. It is necessary to specify the key terminological attributes of the subject in order to proceed with the solution in a specific environment. The discussion will address the question of what methodological approach to choose in the problem analysis, what the specific examples are, and their evaluation in the context of the established terminological dilemmas.
Využití potenciálu zaměstnanců na konkrétních pracovních pozicích jako nástroj zvyšování konkurenceschopnosti firmy
Keywords: potential; job analysis; personnel management; personality; competitiveness